The optimal duration of progesterone supplementation in pregnant women after IVF/ICSI: a meta-analysis - Liu Xi-Ru; Mu Hua-Qiao; Shi Qi; Xiao Xiao-Qiu; Qi Hong-Bo (BMC, 2012)
Abstract Background Progesterone supplementation after in vitro fertilisation/intracytoplasmic sperm injection (IVF/ICSI) can improve the rates of clinical pregnancy and live birth, but the optimal duration of treatment remains controversial. The objective of this meta-analysis was to investigate the effects of early progesterone cessation on pregnancy outcomes in women undergoing IVF/ICSI. Methods We searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), the Chinese biomedicine (CBM) literature database, and the Wanfang database. The final search was performed in July 2012. All available randomised trials that compared the effects of early progesterone cessation with progesterone continuation during early pregnancy after IVF/ICSI were included. The main outcome measures were live birth rate, miscarriage rate and ongoing pregnancy rate. Fixed or random-effects models were chosen to calculate the risk ratio (RR). Results Six eligible studies with a total of 1,201 randomised participants were included in the final analysis. No statistically significant differences were detected between patients who underwent early progesterone cessation and those who received progesterone continuation for luteal phase support in terms of live birth rate (RR: 0.95, 95% CI: 0.86-1.05), miscarriage rate (RR: 1.01, 95% CI: 0.74-1.38) or ongoing pregnancy rate (RR: 0.97, 95% CI: 0.90-1.05). These results did not change after a sensitivity analysis. Conclusions The currently available evidence suggests that progesterone supplementation beyond the first positive hCG test after IVF/ICSI might generally be unnecessary, although large-scale randomised controlled trials are needed to strengthen this conclusion.